Homer1a Attenuates Hydrogen Peroxide-Induced Oxidative Damage in HT-22 Cells through AMPK-Dependent Autophagy - Wu, Xiuquan; Luo, Peng; Rao, Wei; Dai, Shuhui; Zhang, Lei; Ma, Wenke; Pu, Jingnan; Yu, Yang; Wang, Jiu; Fei, Zhou (Frontiers in Neuroscience, 2018)
Neuronal oxidative stress is involved in diverse neurological disorders. Homer1a, as an important member of the Homer family and localized at the postsynaptic density, is known to protect cells against oxidative injury. However, the exact neuroprotective mechanism of Homer1a has not been fully elucidated. Here, we found that Homer1a promoted cell viability and reduced H2O2-induced LDH release. The overexpression of Homer1a enhanced autophagy after H2O2 treatment, which was confirmed by increased expression of LC3II, Beclin-1 and greater autophagosome formation. In addition, we demonstrated that activating autophagy improved cell survival and reduced H2O2-induced oxidative stress and mitochondrial damage. Moreover, the autophagy inhibitor 3-MA partially prevented the protective effects of Homer1a against oxidative challenge. We also found that the upregulation of Homer1a after H2O2 treatment increased the phosphorylation of AMPK. Furthermore, the AMPK inhibitor compound C inhibited Homer1a-induced autophagy and abolished Homer1a-mediated neuroprotection. All the above data suggests that Homer1a confers protection against H2O2-induced oxidative damage via AMPK-dependent autophagy.